Genome-wide association studies identify miRNA-194 as a prognostic biomarker for gastrointestinal cancer by targeting ATP6V1F, PPP1R14B, BTF3L4 and SLC7A5 - Huang, Pan; Xia, Lingyun; Guo, Qiwei; Huang, Congcong; Wang, Zidi; Huang, Yinxuan; Qin, Shanshan; Leng, Weidong; Li, Dandan (Frontiers in Oncology, 2022)
The dysregulated genes and miRNAs in tumor progression can be used as biomarkers for tumor diagnosis and prognosis. However, the biomarkers for predicting the clinical outcome of gastrointestinal cancer (GIC) are still scarce. In this work, we identified 9 prognostic miRNAs for GIC by global microRNA expression analysis. Among them, miR-194 was the only one miRNAs that significantly associated with overall survival, disease-specific survival and progress-free interval in both gastric, colorectal and liver cancers, indicating miR-194 was an optimal prognostic biomarker for GIC. By analyzing two independent transcriptome data, a total of 18 conservative target genes of miR-194 were identified. Genome-wide CRISPR-cas9 proliferation screening assay furthermore confirmed that four genes downregulated by miR-194, including ATP6V1F, PPP1R14B, BTF3L4 and SLC7A5, were required for cell proliferation. Ago-HITS-CLIP-seq analysis further confirmed that ATP6V1F, PPP1R14B, BTF3L4 and SLC7A5 were directly targeted by miR-194. Gene expression correlation analysis, western blotting assay and cell proliferation assay together validated that miR-194 inhibits cell proliferation by targeting ATP6V1F, PPP1R14B, BTF3L4 and SLC7A5 in GIC. In summary, miR-194 is an optima biomarker for predicting the outcome of GIC. Our finding highlights that miR-194 exerts a tumor-suppressive role in digestive system cancers by targeting ATP6V1F, PPP1R14B, BTF3L4 and SLC7A5.